Impaired Glucose Metabolism Despite Decreased Insulin Resistance After Renal Transplantation - Manfred Hecking; Alexander Kainz; Johannes Werzowa; Michael Haidinger; Andrea Tura; Angelo Karaboyas; Walter H. Hörl; Michael Wolzt; Giovanni Pacini; Friedrich K. Port; Marcus D. Säemann (The Korean Society of Nephrology, 2012)
The pathophysiology underlying new-onset diabetes after transplantation (NODAT) is unresolved. We obtained demographics and laboratory data from all 1064 renal transplant recipients followed at our outpatient clinic in 2009/2010, randomly assigned 307 patients without previously diagnosed diabetes to a routine 2-hour oral glucose tolerance test (OGTT), and compared the metabolic results to a large, unrelated cross-sectional cohort of non-transplanted subjects. Among renal transplant recipients, 11% had a history of NODAT, and 12% had type 1 and type 2 diabetes. 42% of all OGTTs were abnormal (9% diabetic), predominantly in older patients who received tacrolimus. Compared to non-transplanted subjects, basal glucose was lower and HbA1c higher in renal transplant patients. Compared to non-transplanted subjects, insulin secretion was inferior, and insulin sensitivity improved at ≥6 months, as well as 3 months post-transplantation:(The Figure shows linear spline interpolation; all p for overall difference between non-Tx and Tx patients <0.02, using likelihood ratio testing). Our results indicate that impaired insulin secretion is the predominant problem after renal transplantation, suggesting benefit for therapeutic regimens that preserve beta cell function after renal transplantation. The mechanism of increased insulin sensitivity might be pathophysiologically similar to pancreatogenic diabetes.fx1